Evaluation of plant characteristics and disease resistance in Cu-ipt transformed watermelon cv. crimson sweet - Goktepe, Fahrettin, author; Hughes, Harrison G., advisor; Byrne, Patrick F., committee member; Vivanco, Jorge M., committee member; Hill, Joseph P., committee member (Colorado State University. Libraries, 2004)
Watermelon cv. Crimson Sweet was transformed with the copper inducible isopentenyl transferase gene (Cu-ipt) via Agrobacterium mediated gene transformation process. The ipt gene governs the rate-limiting step in the cytokinin biosynthesis pathway. The transformants were confirmed via polymerase chain reaction (PCR) in the plant with ipt specific primers. Cu-ipt transformed plants were treated with copper sulfate at a concentration of 5, 10, or 50 μM copper sulfate to determine if the gene could be activated by copper at three levels. Transformed plants treated with copper sulfate differed in evaluated horticultural characteristics from those non-transformed as well as transformed plants not sprayed with copper sulfate. Delayed leaf senescence, increased chlorophyll content, reduced apical dominancy and released axillary buds were significantly different in Cu-ipt transformants compared to non-transformant plants. Significant reduction of seed number in watermelon fruit was also observed in copper sulfate treated Cu-ipt plants as compared to the non-transformant plants. Other than some slight alterations, elevated endogenous cytokinin level didn't cause major interference with transformants normal growth and development. The application of copper sulfate also induced resistance against Gummy Stem Blight disease in Cu-ipt transformants and their seedlings compared to the non-transformant plants.
Covers not scanned.
Keywords: Watermelons -- Breeding